Das Ostrauer Industriegebiet in der Kriegswirtschaft des Dritten Reiches 1938 - 1945 - Grobelný, Andělín (Studia Historiae Oeconomicae, 1979)
This study examines the economic development and strategic importance of the Ostrava industrial region within the Nazi German war economy between 1938 and 1945. The starting point is the Munich Agreement of 1938, which led to the territorial fragmentation of the region. The industrial core around Moravská Ostrava was cut off from key supply and transport networks, with far-reaching consequences for production capacity, labor availability, and economic autonomy. The aim of the study is to analyze the political, economic, and social transformations in the region during its occupation by the Third Reich. The author draws on contemporary documents, official memoranda, archival records, and economic reports to provide a detailed account of the area's integration into the German-controlled war economy. The analysis shows that the Ostrava region was quickly incorporated into the Reich’s economic planning due to its significant coal reserves and coke production – crucial for the German arms industry. Through property transfers, forced administration, and full inclusion in the Nazi command economy, the region was systematically subordinated to German war needs. Key findings concern the Germanization of industrial enterprises, the widespread use of forced labor, intensive resource exploitation, and the growing dominance of German corporations such as the Göring Works and Deutsche Bank. Despite heavy structural interventions and occupation policies, the Ostrava industrial zone remained a key industrial engine of the Reich until the end of the war.